As contradições da disciplina corporal nas séries iniciais do ensino fundamental: Uma análise a partir da teoria crítica da sociedade - Oliveira, Luciane Paiva Alves de (2006)
This is an empirical research that analyzes the possible contributions corporal discipline may give to the formation process carried out in schools. Through a theoretical reflection it indicates that the discipline of body can appear as a potential element during the individuals cultural formation, thus collaborating so they can have access to knowledge that will allow them to think about those aspects that build up society. Nevertheless, it proposes to investigate if this fact is really accomplished during the students school lives. This research was executed by following-up teachers activities, as well as the trajectory of three students along the first part of cycle II of elementary teaching (the former third year of primary school). This study was performed in an Integral Education Center that belongs to Curitiba s municipal school system and the investigation focused on the Portuguese, gymnastics, mathematics, history/geography and arts classes. Data collection was made by means of observation, interviews and student evaluation school documents. The analysis used studies by Michel Foucault, but focused, fundamentally, on the contributions made by some authors of the Critical Theory of Society, especially Herbert Marcuse, Max Horkheimer and Theodor W. Adorno. In this sense, this research confirmed the hypothesis that, within school ambit, corporal discipline can be adjusted to performance instrumental interests, as well as to benefit the individuals reflexive formation, once it can help them to collect and communicate knowledge. Finally, there is the conclusion that those contradictions identified around corporal discipline are related to the ambiguities from the formation, itself, realized in this society